Learning Beyond Limits: A Literature Review on Educational Facilities and Student Achievement in 3T Regions - Hidayatussa'adah Hidayatussa'adah; Eko Budi Santoso (Pedagogia: Jurnal Ilmiah Pendidikan, 2025)
The disparity in education quality between urban areas and underdeveloped regions such as Maluku and Papua remains a critical issue in Indonesia. Limited educational facilities, such as classrooms, laboratories, and internet access are often perceived as major barriers to academic achievement. However, the success of students from these regions in national competitions like the Academy of Champions (AoC) by Ruangguru suggests that physical limitations do not necessarily hinder academic excellence. This study aims to examine how educational facility management can be effectively implemented under constrained conditions in 3T regions. Using a literature review method with a descriptive analytical approach, this research explores various secondary sources that highlight educational management practices in Maluku and Papua. The findings reveal that functional-based management, community participation, the use of educational technology, and adaptive school leadership are key success factors. The study concludes that limitations can be overcome through contextual and innovative managerial approaches, as well as through collaboration between schools, communities, and digital tools to create productive and inclusive learning environments.